Impact of COVID-19 on education sector in Pakistan (A case of Punjab Group of Colleges) - Ayyub, Muhammad Furqan; Asghar, Adnan; Arshad, Hafiz Muhammad Jawad (Advances in Social Sciences Research Journal, 2022)
On 20thMarch, 2020 because of vide spread of COVID-19, the individuals were advised for isolation at home considering the lockdown of educational institutes. This caused economic barren and lack of learning and knowledge globally. As a result, Pakistan was at the top level worldwide for closure of schools during CORONA virus (COVID-19).For elimination of its adverse effects, The Government of Pakistan rapidly started effective strategies. The development and implementation of different tools for students to facilitate in their studies proved a great milestone for PGC. Microsoft teams for online lectures, recorded lectures, video audio conversations between students and teachers, special test system to gain competitive edge managed the situation during this COVID 19.